Neural pathways in nutrient sensing and insulin signaling - Ratnaparkhi, Anuradha; Sudhakaran, Jyothish (Frontiers in Physiology, 2022)
Nutrient sensing and metabolic homeostasis play an important role in the proper growth and development of an organism, and also in the energy intensive process of reproduction. Signals in response to nutritional and metabolic status is received and integrated by the brain to ensure homeostasis. In Drosophila, the fat body is one of the key organs involved in energy and nutrient sensing, storage and utilization. It also relays the nutritional status of the animal to the brain, activating specific circuits which modulate the synthesis and release of insulin-like peptides to regulate metabolism. Here, we review the molecular and cellular mechanisms involved in nutrient sensing with an emphasis on the neural pathways that modulate this process and discuss some of the open questions that need to be addressed.